PENGARUH PENDIDIKAN DAN PRAKTIK KEWIRAUSAHAAN TERHADAP MINAT MAHASISWA UNTUK BERWIRAUSAHA (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Puji Astuti; Abdul Qodir Djaelani; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis research is to know the Influence of Education and Entrepreneurship Practices on Student Interest for Entrepreneurship.This research is explanatory research. Respondents in this study were all students of the Faculty of Economics and Business of Islamic University of Malang. The sample used in this research is 97 students. The data collection method used is by distributing questionnaires and documentation. Data analysis using instrument test, normality test, classical assumption test, multiple regression analysis, hypothesis test, and coefficient of determination.Based on the results of research can be concluded that the partial variables of education and entrepreneurial practice variables there is a significant influence on student entrepreneurship interests. And simultaneously education and entrepreneurship practices have an influence on student entrepreneurship interest.Keywords: Education, Entrepreneurship Practices, Students, Interest in Entrepreneurship